Effect of DER, ROA, ROE, EPS and MVA on Stock Prices in Sharia Indonesian Stock Index - Martina Rut Utami; Arif Darmawan (Pusat P2M Politeknik Negeri Batam, 2019)
The research examine the effect of debt to equity ratio, return on assets, return on equity, earning per share, market value added on stock prices in manufacturing companies listed in Indonesian Sharia Stock Index. The purposive sampling method is used in our research, resulted 53 companies as the samples with 265 observations. The research used data during 2012-2016 from Indonesia Stock Exchange database with panel data analysis. The research found that, earning per share and market value added have a positive effect on stock prices, but different results for the variables debt to equity ratio, return on assets and return on equity partially have no effect on stock prices.